ANALISIS PEMANFAATAN RUANG WISATA SPTN 1 TAMAN NASIONAL BROMO TENGGER SEMERU MENUJU DESTINASI YANG BERKELANJUTAN - Yanuar Firmansyah; Luchman Hakim; Ari Darmawan (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This research uses descriptive methode using qualitative approach with two formulations of problem : (1) How is the use of space in the lanscape view points in SPTN I Bromo Tengger Semeru National Park? (2) How is the tourists' perceptions towards the comfort in the lanscape view points in SPTN I Bromo Tengger Semeru National Park?. The data sources are obtained by interview,